Minority Football Coaches' Diminished Careers: Why is the "Pipeline" Clogged?1. (6th December 2012) - Bozeman, Barry; Fay, Daniel
<x xml:space="preserve">Abstract</x> Objectives Research on minority representation and career trajectories in higher education represents a substantial body of evidence in the field; however, the empirical evidence fails to address a crucial area: intercollegiate athletics. This study aims to address the gap in the empirical work and study the career trajectories and representation of African‐Americans and Latinos in NCAA FBS football coaching positions. Methods A pipeline argument is often utilized to explain the underrepresentation of minorities in certain careers and industries. This pipeline argument is erroneous in this instance because of the number of minority players in college football that make up the "future coach career pool." We develop a position hierarchy in which previous assistant coaching positions are seen as stepping stones to an ultimate head coaching position. Results We find that white and minorities coaches have different career trajectories and position hierarchies that ultimately lead to the underrepresentation of minorities at the head coaching ranks. Conclusions Evidence suggests sharp differences in the likelihood of certain player positions and, in turn (and likely related), certain coaching positions to achieving head coach. The career utility hierarchy developed here seems to have some validity and, most important for present purposes, shows some considerable difference in the career stepping stones of, respectively, whites and minorities.